Dilemma of Competitive Equality: Transgender vs Cisgender Athletes in Women's International Sports Competition - Raden, Maulana Damarjati (International Law Department, Faculty of Law Universitas Padjadjaran, 2023)
This research aims to solve the human rights issue of the participation of transgender female athletes in international sports competitions in the women's division. The existence of transgender female athletes yields two perspectives: inclusivity as a human right for transgender female athletes and unfair competition for cisgender female athletes. This issue occurs due to the physiological advantages possessed by a transgender female athlete from the high level of testosterone they have, which creates unfairness in sports competition for cisgender female athletes, and the policies of international sports organizations that exclude the participation of transgender female athletes who have experienced puberty to take part in international sports competitions. Several controversial cases have sparked debate in the international community, such as the Tiffany Newel case in the running competition and the Lia Thomas case in the swimming competition; both are female transgender athletes who won sports competitions in the women's division. Although a transgender individual already has inherent human rights regulated through international law, these rights could not be a basis that overrides the rights and freedoms of other people. In this case, the right to equal and safe competition for cisgender women. The solution to this problem is to develop an 'open category' which aims to ensure the participation of all world athletes in sports competitions regardless of gender or gender identity.